Homoclinic Solutions for a Class of the Second-Order Impulsive Hamiltonian Systems - Jingli Xie; Zhiguo Luo; Guoping Chen (Abstract and Applied Analysis)
This paper is concerned with the existence of homoclinic solutions for a class of the second order impulsive Hamiltonian systems. By employing the Mountain Pass Theorem, we demonstrate that the limit of a 2kT-periodic approximation solution is a homoclinic solution of our problem.